Drawing masterclass landscapes - Eggleton, Margaret (Tunbridge Wells search press, 2015)
Artists of all skill levels will find much to inspire them in this detailed and practical guide. Margaret Eggleton takes us through easy-to-follow drawing stages, and includes advice on using sketchbooks, line and tone, perspective and more. She shows how to draw elements of the landscape such as trees and foliage, hills and mountains, skies, water and buildings, including step by step exercises throughout
13
Keywords: Art and Design; Landscape drawing -- Technique; landskaber